PENGARUH PENERAPAN DISIPLIN DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN RUMAH SAKI IBU DAN ANAK (RSIA) ERIA BUNDA PEKANBARU - Darni Yuanita Siallagan; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
An important problem faced by leaders in hospitals is how to maintain loyalty so that they can support the success of achieving goals. The hospital strives to maintain quality employees so that they work for a long time in the hospital is one of the goals of the hospital. This research was conducted at RSIA Eria Bunda Pekanbaru. The purpose of this study was to determine the effect of work discipline and work motivation on employee loyalty at RSIA Eria Bunda Pekanbaru. Work discipline and work motivation as independent variables (X1, X2) while employee loyalty as the dependent variable (Y) The problem in this research is the occurrence of fluctuating employee turnover and employee absenteeism accompanied by high employee absenteeism. It can be seen from the data on Labor Turn Over and company absenteeism. The sample of this study was taken as many as 42 respondents from the population calculated using the Slovin formula. The data obtained from the questionnaire results and then processed for later statistically tested through the SPSS program. From the results of the tests conducted, it shows that work discipline and work motivation have a positive and significant effect on employee loyalty at RSIA Eria Bunda Pekanbaru. Keywords: Work Discipline, Work Motivation, And Employee Loyalty